Mediastinal Teratoma with Neuroendocrine Features in 34-Year-Old Male with Syncope - Peter A. Andrawes; Masood A. Shariff; Qing Chang; Fanyi Kong; Frank M. Rosell (Case Reports in Surgery)
Neuroendocrine tumors that arise in an extragonadal teratoma are extremely rare. Somatic-type malignancy, defined as any sarcoma, carcinoma, leukemia, or lymphoma developing in a germ cell tumor, occurs in approximately 2% of all germ cell tumors. Our case represents a mediastinal mass that was incidentally found in a patient with syncope. Surgical resection confirmed mature teratoma with neuroendocrine features.